Appropriateness of the metabolic equivalent (MET) as an estimate of exercise intensity for post-myocardial infarction patients. Issue 1 (11th January 2017) - Woolf-May, Kate; Meadows, Steve
Abstract : Aims: To explore: (1) whether during exercise metabolic equivalents (METs) appropriately indicate the intensity and/or metabolic cost for post-myocardial infarction (MI) males and (2) whether post-exercise VO2 parameters provide insight into the intensity and/or metabolic cost of the prior exercise. Methods: 15 male phase-IV post-MIs (64.4±6.5 years) and 16 apparently healthy males (63.0±6.4 years) participated. Participants performed a graded cycle ergometer test (CET) of 50, 75 and 100 W, followed by 10 min active recovery (at 50 W) and 22 min seated recovery. Participants' heart rate (HR, bpm), expired air parameters and ratings of perceived exertion (exercise only) were measured. Results: General linear model analysis showed throughout significantly lower HR values in post-MI participants that were related to β-blocker medication ( F (2, 5) =18.47, p<0.01), with significantly higher VCO2 /VO2 ( F (2, 5) =11.25, p<0.001) and gross kcals/LO2 /min ( F (2, 5) =11.25, p<0.001). Analysis comparing lines of regression showed, during the CET: post-MI participants worked at higher percentage of their anaerobic threshold (%AT)/MET than controls ( F (2, 90) =18.98, p<0.001), as well as during active recovery (100–50 W) ( F (2, 56) =20.81, p<0.001); during seated recovery: GLM analysis showed significantly higher values of VCO2 /VO2 for post-MI participants compared with controls ( F (2, 3) =21.48, p=0.001) as well as gross kcals/LO2 /min ( F (2, 3) =21.48, p=0.001). Conclusion: Since METs take no consideration of any anaerobic component, they failed to reflect the significantly greater anaerobic contribution during exercise per MET for phase-IV post-MI patients. Given the anaerobic component will be greater for those with more severe forms of cardiac disease, current METs should be used with caution when determining exercise intensity in any patient with cardiac disease.